Studi Literatur Pelaksanaan Crowdfunding Oleh Public Figure Melalui Platform kitabisa.com - Ketut Ajeng Sespiani; Monica Apilia; Shepriyani Miftajanna (CV. ITTC INDONESIA, 2021)
The development of technology, especially the internet, provides many conveniences and benefits for its users. Starting from the ease of accessing information to carrying out various activities in the field of marketing to be more efficient with the presence of the internet. One of them is the existence of social media which has now become a forum for people to make a living, such as by influencers or celebrities. To be able to persuade their followers, a good influencer must be able to do the right personal branding. Crowdfunding is one way that influencers can do personal branding. Through the crowdfunding implementation, an influencer can build good personal branding and on the other hand, the credibility of the influencer can increase the credibility of the crowdfunding platform which can encourage the audience to get involved in fundraising. A qualitative approach using the systematic review method, researchers used in this study to determine the effectiveness of the crowdfunding implementation by a public figure in this study, Awkarin through the Kitabisa.com platform as an effort to build good personal branding and maximizing the implementation of fundraising. itself. The results of this study reveal that the online donation program that Awkarin runs through the Kitabisa.com platform is the right and effective way to build her personal branding and in maximizing the fundraising program she is running